The Employment of Historical Symbolism by the Poets of the Seventies Generation:)Khazal Al-Majidi as a Model( - JAbbar Nassr, Nadam ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Every era has its own history, every generation its time, and every art form its characteristics. This is evident in the poets of the seventies generation. During this period, many poets emerged whose poetry was deeply immersed in the use of symbolism as an equivalent to reality and a means of expressing it. The employment of symbolism had its motives and reasons, prompting poets to utilize symbols to convey societal issues. Among the most significant symbols frequently employed by poets was the historical symbol, as it represents a glorious past and a rich heritage. Through the evocation of the past in the present, the poet attempts to express a future vision. This was particularly evident in the works of one of the most prominent poets of this generation, Khazal Al-Majidi. His poetry abounded with various symbols, the most notable of which was the historical symbol. This inclination may be attributed to his academic specialization, as he is an expert in ancient history